Trends in the delivery route of twin pregnancies in the United States, 2006–2013. (October 2016) - Bateni, Zhoobin H.; Clark, Steven L.; Sangi-Haghpeykar, Haleh; Aagaard, Kjersti M.; Blumenfeld, Yair J.; Ramin, Susan M.; Lee, Henry C.; Fox, Karin A.; Moaddab, Amirhossein; Shamshirsaz, Amir A.; Salmanian, Bahram; Hosseinzadeh, Pardis; et al.
Abstract: Objectives: To determine the trends of cesarean delivery rate among twin pregnancies from 2006 to 2013. Study design: This is a population-based, cross-sectional analysis of twin live births from United State birth data files of the National Center for Health Statistics for calendar years 2006 through 2013. We stratified the population based on the gestational age groups, maternal race/ethnicity, advanced maternal age (AMA) which was defined by age more than 35 years and within the standard birth weight groups (group 1: birth weight 500–1499 g, group 2: birth weight 1500–2499 g and group 3: birth weight >2500 g). We also analyzed the effect of different risk factors for cesarean delivery in twins. Results: There were 1, 079, 102 infants born of twin gestations in the U.S. from 2006 to 2013, representing a small but significant increase in the proportion of twin births among all births (3.2% in 2006 versus 3.4% in 2013). The rate of cesarean delivery in twin live births peaked at 75.3% in 2009, and was significantly lower (74.8%) in 2013. The rate of the twin live birth with the breech presentation increased steadily from 26.3% in 2006 to 29.1% in 2013. For the fetus of the twin pregnancy presented as breech, the cesarean delivery rate peaked at 92.2% in 2010, falling slightly but significantly in the ensuing 3 years. The results demonstrated that the decrease in cesarean delivery rate was due to fewer cesareans in non-Hispanic white patients; all other ethnic subgroups showed increasing rates of cesarean delivery throughout the study. Gestational diabetes, gestational hypertension, previous cesarean delivery and breech presentation were all significant risk factors for cesarean delivery during the entire study period. Induction of labor and premature rupture of the membranes were associated with lower rates of cesarean delivery in twins. Conclusion: The recent decrease in the cesarean delivery rate in twin gestation appears to be largely attributable to a decline in cesarean among pregnancies complicated by breech presentation in non-Hispanic white women, and may reflect a health care disparity that deserves further research.